Economic and ecological perspectives of farmers on rice insect pest management - M.T.N. Cabasan; J.A.G. Tabora; N. Cabatac; C.M. Jumao-as; J.O. Soberano; J.V. Turba; N.H.A. Dagamac; E. Barlaan (Global Journal of Environmental Science and Management)
Understanding farmers’ perception is important in the development of sustainable and cost-effective integrated pest management strategies. Hence, farmers’ perception on rice insect pests and pesticide use was evaluated by selected 112 farmers composed of 77% males and 23% females, over the rice growing areas of North Cotabato, Central Mindanao, Philippines. 62% of farmers that were interviewed use pesticides based on the presence of pests. These farmers identified white stem borer and rice leaf folder as the most encountered insect pests on the local rice crops. Due to these insect pests, rice production became constrained producing low income for the farmers. Pesticide application was perceived to be effective (73%) but not efficient in controlling insects. Moreover, farmers recognized the negative effects of pesticide applications in the environment (76%). However, in spite of these expensive pest control strategies, local farmers still agreed (83%) to apply these methods to increase rice production and their income. With the advantage of using pesticides to boost production over the harm it can cause, farmers would not agree to stop (39%) or still are undecided (23%) to reduce pesticide application. Thus, efficient, safe, low cost pest control strategies are needed to reduce reliance of farmers to pesticides and to improve agricultural production and food security of smallholder farmers in the Philippines.